Design and Implementation of Instructional Message Design for Online Learning in Postgraduate Programmes at Open University Malaysia - Zahari Hamidon (2021)
Open University Malaysia (OUM) has offered blended and online learning for almost 19 years since it was established in 2001. The long journey of providing the two modes of education has matured in offering online learning to learners. The learning process in an online learning environment is complicated for online learners due to the lengthy learning structure. Long learning structures affect online learners in terms of performing many tasks. A proper instructional strategy will make a meaningful learning structure with a significant task. The learning resources’ design and development are considered part of the backend process before the learning process. Some resources might not work due to a lack of pedagogical input during the design process. Message design with proper pedagogical strategies can be part of the activity in lesson design that contribute the information required by the learner to perform specific tasks. In performing the task, the learner tends to interact aggressively through the medium. The learner’s cognitive ability for the learning resources is among the issues that need to be resolved. This study intends to determine an essential indicator in designing an interactive online learning prototype (IOLP). The development of an IOLP is based on the message design logic by Hullman (2004) and Petterson (2012). The task in IOLP is designed based on an adaptive learning approach. This study reports on the effects of the components in IOLP synthesised from Hullman (2004) and Petterson (2012) that are translated into the learning process embedded into appropriate pedagogical input. The analytic learning data from the Moodle-based Learning Management System report is used to measure the learner’s cognitive ability on IOLP. The findings show that learners with more effort in performing the tasks laid out in IOLP will gain the highest score compared to those with less effort. (Abstract by author)